Analysis of students' mathematical literacy on online learning in terms of self-efficacy - Yulianah, Lia; Supratman, Supratman; Rahayu, Diar Veny (Desimal: Jurnal Matematika, 2022)
The purpose of this research is to analyze how students' mathematical literacy skills in online learning are viewed from self-efficacy. The method used in this research is a qualitative method with an analytical descriptive design. Data was collected using a self-efficacy questionnaire consisting of positive and negative statements and a mathematical literacy test. Data analysis was carried out by classifying students' self-efficacy into high, medium, and low categories by selecting 2 students for each category with the help of Microsoft Excel. Based on these data, it was found that students who had high self-efficacy were able to answer mathematical literacy questions on the indicators of formulating, using, and interpreting, but not completely and systematically. Students with medium self-efficacy are only able to complete level 1 mathematical literacy on indicators to formulate accurately, completely, and systematically. Students who have low self-efficacy are not able to solve mathematical literacy problems completely and systematically.